New Plastitar Record for the Mediterranean Sea: Characterization of Plastics and Tar from the Salento Peninsula (Ionian Sea) - Silvia Fraissinet; Emanuele Mancini; Chiara Funiati; Caterina Martino; Giuseppe Egidio De Benedetto; Chiara Roberta Girelli; Francesco Paolo Fanizzi; Genuario Belmonte; Stefano Piraino (Toxics)
The various forms of anthropogenic pollution are regarded as a serious threat to marine coastal areas. The overproduction and mismanagement of petroleum derivatives, such as tar and plastics, have resulted in a significant correlation between these two pollutants. The aggregation of tar, microplastics (MPs), and natural materials can create plastitar blocks, which are common in coastal areas. These raise concern about the undeniable negative impact on the marine ecosystem and the associated biota, and serve as a recognizable and understandable indication of environmental decline. Here, the composition of the 11 plastitar blocks collected on the Ionian side of the Apulia region (Italy) was characterized both in tar and plastics using nuclear magnetic resonance (NMR) spectroscopy and Fourier transform infrared (FTIR) spectroscopy, respectively. Of the 250 particles extracted from the tar, 208 were identified as plastics, predominantly Polyethylene. The majority of these were in the form of pellets (90%), with fragments accounting for 5% and films and filaments representing the remaining 5%. This study provides new data that can be used to enhance the understanding of the distribution and baseline information about this novel form of pollution in Italian waters.